Analisis Pada Iklan Televisi: Diksi dan Gaya Bahasa Anafora - Tuty Kusmaini (Kelasa, 2018)
Advertising is a form of message about a product or service delivered through the media and aimed at the community. Advertising can be analyzed through the use of diction and language style. The problems that will be discussed in this paper is how the diction and style of anaphoric language in domestic private television advertisements. The aims of this paper is to describe the form of word choice or diction and anaphoric language style in television advertisements. This paper uses analytical and prescriptive descriptive methods. The data source used is obtained through the recording of audiovisual advertisements which are categorized as commercial advertisements. Samples taken in the form of selected advertisements that use diction and anaphoric language style that stands out so that it can be analyzed using diction and anaphoric language style. The Techniques of collection data that used in this paper are recording techniques, see and note. This study paper was analyzed using interactive analysis. Based on the method used, the results of the research were obtained in the form of word choice or diction and anaphoric language style used in television advertisements. Dictions used include the use of connotative words, the use of personal pronouns, the use of foreign terms (English, the use of speech words, beheading of consonants at the beginning of the word, and the use of short terms. The use of anaphorical language in domestic private television commercials serves to provide an affirmation Anaphoric language style is used to provide attractiveness and convince consumers of the products offered. AbstrakIklan merupakan bentuk pesan tentang suatu produk atau jasa yang disampaikan melalui media dan ditujukan kepada masyarakat. Iklan dapat dianalisis melalui penggunaan diksi dan gaya bahasanya. Masalah yang dibahas dalam tulisan ini adalah bagaimanakah diksi dan gaya bahasa anafora pada iklan televisi swasta dalam negeri. Tulisan ini bertujuan untuk mendeskripsikan bentuk pilihan kata atau diksi dan gaya bahasa anafora pada iklan televisi.Penelitian ini menggunakan metode deskriptif analitik dan preskriptif. Sumber data yang digunakan diperoleh melalui hasil rekaman iklan audiovisual yang dikategorikan sebagai iklan komersial. Sampel yang diambil berupa iklan terpilih yang menggunakan diksi dan gaya bahasa anafora yang menonjol sehingga dapat dianalisis pemakaian diksi dan gaya bahasa anaforanya. Teknik pengumpulan data yang digunakan dalam penelitian ini berupa teknik rekam, simak dan catat. Penelitian ini dianalisis menggunakan analisis interaktif. Berdasarkan metode yang digunakan, diperoleh hasil penelitian berupa bentuk pilihan kata atau diksi dan gaya bahasa anafora yang digunakan pada iklan televisi. Diksi yang digunakan meliputi pemakaian kata konotatif, pemakaian kata ganti orang, pemakaian istilah asing (bahasa Inggris), pemakaian kata tutur, pemenggalan konsonan di awal kata, dan pemakaian istilah singkat. Penggunaan gaya bahasa anafora pada iklan televisi swasta dalam negeri berfungsi untuk memberi makna penegasan. Gaya bahasa anafora digunakan untuk memberikan kemenarikan serta meyakinkan konsumen terhadap produk yang ditawarkan.